2016
DOI: 10.1039/c5tc02751a
|View full text |Cite
|
Sign up to set email alerts
|

Electrically conductive thermoplastic elastomer nanocomposites at ultralow graphene loading levels for strain sensor applications

Abstract: Strain sensors with high sensitivity are reported in the thermoplastic polyurethane nanocomposites with ultralow graphene loading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
313
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 515 publications
(325 citation statements)
references
References 63 publications
7
313
0
5
Order By: Relevance
“…Here, a gauge factor (GF = (DR/R 0 )/e, where DR/R 0 is the responsivity of the porous CPC foam and e is the compression strain) can be introduced to evaluate the sensitivity of the strain sensor. 4,36,60 It can be seen that the GFs at the strain rates of 1, 3 and 5 mm min À1 are about 0.82, 1.28 and 2.32, respectively, indicate that a higher strain rate brings about higher strain sensitivity. This is mainly because that the porous CPC foam suffered a larger compression stress at a higher compression rate (Fig.…”
Section: Piezoresistive Behavior Of Porous Graphene/tpu Foamsmentioning
confidence: 90%
See 1 more Smart Citation
“…Here, a gauge factor (GF = (DR/R 0 )/e, where DR/R 0 is the responsivity of the porous CPC foam and e is the compression strain) can be introduced to evaluate the sensitivity of the strain sensor. 4,36,60 It can be seen that the GFs at the strain rates of 1, 3 and 5 mm min À1 are about 0.82, 1.28 and 2.32, respectively, indicate that a higher strain rate brings about higher strain sensitivity. This is mainly because that the porous CPC foam suffered a larger compression stress at a higher compression rate (Fig.…”
Section: Piezoresistive Behavior Of Porous Graphene/tpu Foamsmentioning
confidence: 90%
“…5(b)). 4 With the addition of graphene, the peak intensity at 1730 cm À1 becomes weaker; in addition, the peak at 1700 cm À1 also becomes less obvious and a new weak peak at 1969 cm À1 appears gradually. The interaction between the N-H bond of TPU and the remaining oxygenated groups of graphene accounts for the variation of FT-IR spectra.…”
mentioning
confidence: 99%
“…3 . 3 S t i m u l u s -r e s p o n s i v e e l a s t o m e r s e n s o r s a n d a c t u a t o r s Stimuli-responsive elastomers refer to elastomers that can respond to external stimuli, such as electricity [21], strain [9,[158][159][160], temperature [161] and solvent [162][163][164], as indicated by electrical conductivity behavior.…”
Section: 2 2 3 2 S T R E T C H a B L E E L A S T O M E R C O N mentioning
confidence: 99%
“…Polymer composites with GO have attracted great interest due to their unique properties, which are derived from extended interactions between the GO and the matrix and their wide potential applications such as electromagnetic wave shielding and sensors [24][25][26][27][28][29][30][31][32]. For example, Cao et al [33] found that the tensile strength and young's modulus of GO composites increased by 78 and 73%, respectively, when compared with pure polystyrene.…”
Section: Introductionmentioning
confidence: 99%